NILAI WISATAWAN DAN REPUTASI DESTINASI SERTA DAMPAKNYA PADA CUSTOMER SHARE DI BANDUNG RAYA - Rahma Wahdiniwaty (Indonesian Journal of Economics and Business, 2012)
Tourism is one industry that can enhance economic growth. GDP contribution of the tourism industry is likely to decline and result in lower customer share of tourists and the destinatiohas a low positive reputation, which in turn decreased the PAD,. Aim of this study to assess and analyze the value and reputation of the tourist destinations and the impact on customer share. The method used is survey method, using descriptive analysis and verifikatif. Testing the hypothesis in this study used descriptive and multivariate statistical stratistik using Structural EquationModeling (SEM) considering a model consisting of a number of causal relationships among latent variables, samples were taken with a sampling technique using a Stratified Random Sampling as many as 506 tourists. The results showed that changes in share or share customer rating variable is affected by changes in the value and reputation of the tourist destinations. Bandung Raya value of tourist destinations are superior compared to other tourist destinations have an influence that must be considered in creating high customer share in Bandung Raya. Other factors not studied had a greater influence on customer share compared with the studied variables.